Engineered interfaces between perovskite La2/3xLi3xTiO3 electrolyte and Li metal for solid-state batteries - Yan, Shuo; Al-Salih, Hilal; Yim, Chae-Ho; Merati, Ali; Baranova, Elena A.; Weck, Arnaud; Abu-Lebdeh, Yaser (Frontiers in Chemistry, 2022)
Perovskite La2/3xLi3xTiO3 (LLTO) materials are promising solid-state electrolytes for lithium metal batteries (LMBs) due to their intrinsic fire-resistance, high bulk ionic conductivity, and wide electrochemical window. However, their commercialization is hampered by high interfacial resistance, dendrite formation, and instability against Li metal. To address these challenges, we first prepared highly dense LLTO pellets with enhanced microstructure and high bulk ionic conductivity of 2.1×10^(-4) S cm-1 at room temperature. Then, the LLTO pellets were coated with three polymer-based interfacial layers, including pure (polyethylene oxide) (PEO), dry polymer electrolyte of PEO-LITFSI (lithium bis (trifluoromethanesulfonyl) imide) (PL), and gel PEO-LiTFSI-SN (succinonitrile) (PLS). It is found that each layer has impacted the interface differently; the soft PLS gel layer significantly reduced the total resistance of LLTO to a low value of 84.88 ohm cm-2. Interestingly, PLS layer has shown excellent ionic conductivity but performs inferior in symmetric Li cells. On the other hand, the PL layer significantly reduces lithium nucleation overpotential and shows a stable voltage profile after 20 cycles without any sign of Li dendrite formation. This work demonstrates that LLTO electrolytes with denser microstructure could reduce the interfacial resistance and when combined with polymeric interfaces show improved chemical stability against Li metal.